1992
DOI: 10.1002/abio.370120403
|View full text |Cite
|
Sign up to set email alerts
|

Production of propionic acid by microbiological way. Part 1. Influence of the initial sugars and product concentrations

Abstract: The best yields and productivities of 0.38 g . g-' and 0.35 g . I-' h-I, respectively, for the propionic acid production in a batch system using sugar-cane final molasses as carbon source were obtained when an initial TRS concentration of 50 g . I-' was used.It was obvious that this process is severely inhibited by the acids produced and the most drastic effect (p = 0) was at a TVA concentration near to 250 mmol . I-', independently of the initial TRS concentration employed. A generalizated equation of noncomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Thus, cane molasses is also expected to be a suitable material for propionic acid production. However, the maximum concentration of propionic acid is only 30 g l -1 when cane molasses is used as a carbon source (Obaya et al, 1992;Quesada-Chanto et al, 1994). There remains a need to find an effective process to enhance the propionic acid production from cane molasses.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, cane molasses is also expected to be a suitable material for propionic acid production. However, the maximum concentration of propionic acid is only 30 g l -1 when cane molasses is used as a carbon source (Obaya et al, 1992;Quesada-Chanto et al, 1994). There remains a need to find an effective process to enhance the propionic acid production from cane molasses.…”
Section: Introductionmentioning
confidence: 99%
“…limitation of some important nutrient(s), as cited by OBAYA et aL [17]. Different critical concentrations of propionic acid (acid concentration that suppresses all growth (px = 0)) have been cited.…”
mentioning
confidence: 99%
“…Different critical concentrations of propionic acid (acid concentration that suppresses all growth (px = 0)) have been cited. Using 4 gA yeast extract and whey as the substrate, BLANC and GOMA [15] found 16 g/l and OBAYA et al [17], using 8 gh yeast extract and sucrose as the carbon source, found 13.5-14.0 g/l propionic acid to be the critical concentration. As can be seen in Tab.…”
mentioning
confidence: 99%